Pengenalan Unplugged Coding untuk Anak Usia Dini melalui Pendekatan STEAM di Bayt Al Fath - Imama Lavi Insani (Jurnal Bersama Pengabdian Kepada Masyarakat (SAMAMAS), 2025)
Technological literacy is an essential skill in the digital era, yet introducing programming concepts to early childhood learners requires approaches tailored to their cognitive development. This community service program aimed to introduce the basics of programming through the Unplugged Coding method—teaching computational thinking without digital devices—at Bayt Al Fath Sidoarjo. The program employed interactive games and STEAM-based (Science, Technology, Engineering, Arts, Mathematics) worksheets designed to be modular and accessible for both teachers and parents. The implementation was conducted in three stages: preparation of teaching materials, classroom activities with children, and evaluation through participant observation and formative assessment. Results indicated increased interest and understanding among children in logical sequencing, pattern recognition, and problem-solving. Teachers reported that the worksheets were easy to use and adaptable for independent teaching. This initiative also supported sustainability planning by enabling the development of self-directed learning materials and potential integration into thematic curricula grounded in Islamic values. The program is expected to serve as an innovative, contextual model for early digital literacy education that respects child development principles while equipping learners with essential 21st-century skills.